Action interference in simultaneous and proportional myocontrol: Comparing force- A nd electromyography - Nowak, Markus; Eiband, Thomas; Ramirez, Eduardo Ruiz; Castellini, Claudio (Journal of Neural Engineering, 2020)
Myocontrol, that is, control of a prosthesis via muscle signals, is still a surprisingly hard problem. Recent research indicates that surface electromyography (sEMG), the traditional technique used to detect a subject's intent, could proficiently be replaced, or conjoined with, other techniques (multi-modal myocontrol), with the aim to improve both on dexterity and reliability. Objective. In this paper we present an online assessment of multi-modal sEMG and force myography (FMG) targeted at hand and wrist myocontrol. Approach. Twenty sEMG and FMG sensors in total were used to enforce simultaneous and proportional control of hand opening/closing, wrist pronation/supination and wrist flexion/extension of 12 intact subjects. Main results and Significance. We found that FMG yields in general a better performance than sEMG, and that the main drawback of the sEMG array we used is not the inability to perform a desired action, but rather action interference, that is, the undesired concurrent activation of another action. FMG, on the other hand, causes less interference.
CRIS-Team Scopus Importer:2021-09-13